2021
DOI: 10.1371/journal.pone.0258199
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral alterations in long-term Toxoplasma gondii infection of C57BL/6 mice are associated with neuroinflammation and disruption of the blood brain barrier

Abstract: The Apicomplexa protozoan Toxoplasma gondii is a mandatory intracellular parasite and the causative agent of toxoplasmosis. This illness is of medical importance due to its high prevalence worldwide and may cause neurological alterations in immunocompromised persons. In chronically infected immunocompetent individuals, this parasite forms tissue cysts mainly in the brain. In addition, T. gondii infection has been related to mental illnesses such as schizophrenia, bipolar disorder, depression, obsessive-compuls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 101 publications
3
22
0
Order By: Relevance
“…Acute T. gondii infection is associated with the rapid replication of tachyzoites followed by their conversion to bradyzoites, which can form infectious cysts within the brain, muscle, and other tissues, which establishes a life-long, latent infection ( Sullivan and Jeffers, 2012 ; Rougier et al., 2017 ) that can give rise to neuroinflammation, vascular injury, and damage to the blood–brain barrier ( Castaño Barrios et al., 2021 ; Egorov et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Acute T. gondii infection is associated with the rapid replication of tachyzoites followed by their conversion to bradyzoites, which can form infectious cysts within the brain, muscle, and other tissues, which establishes a life-long, latent infection ( Sullivan and Jeffers, 2012 ; Rougier et al., 2017 ) that can give rise to neuroinflammation, vascular injury, and damage to the blood–brain barrier ( Castaño Barrios et al., 2021 ; Egorov et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, psychiatric and behavioral changes such as schizophrenia ( 13 , 14 ), obsessive-compulsive disorders, personality and bipolar disorders ( 14 ), depression ( 15 ) and alteration of neurocognitive functioning ( 16 ) have been associated with chronic T. gondii infection in human beings. Several studies investigated the influence of T. gondii infection in behavioral and neurocognitive disorders using animal models, replicating aspects present in humans as locomotor alteration ( 17 ), anxiety-like disorder ( 18 22 ), hyperactivity ( 20 , 22 25 ), and also alterations in aversive memory consolidation ( 26 , 27 ), spatial memory loss ( 28 ), and long-term memory impairment ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…In ME-49 T. gondii -infected male B6CBAF1/J mice, behavioral alterations were associated with inflammation-related processes and a continuous increase in cyst load in the CNS ( 34 ). Conversely, a recent study showed that in female C57BL/6 mice ME-49 infection evolves from the early to the long-term chronic phase with reduction of the number, suggestive of gradual infection control, as immune response is established ( 22 ). However, multiple behavioral changes (anxiety-like disorder, depressive-like behavior and hyperactivity) were detected in the early and long-term chronic infection ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations